Equity research - lululemon athletica inc - Cruz, Maria Do Carmo Andrade Farraia Da Graça (2021)
The objective of this equity analysis was to determine whether Lululemon Athleticais under valued or , based on that,make a recommendationto buy, sell or hold.There are no clear guidelines for stock price forecast so,in this research,quantitative (statistical and peers’ analysis)and qualitative approache swere used to calculate the company’s target share price. Lululemon’s revenues, cost of capital and return on invested capital were estimated for the next ten years .Once the forecast was done, the Discounted Cash Flow Model was used to compute the target price.A value of $260.10 was obtained, resulting in a BUY recommendation.